Identification of an Intestinal Microbiota Signature Associated With Severity of Irritable Bowel Syndrome - Simrén, Magnus (University of Gothenburg, 2019)
Data from the publication Identification of an Intestinal Microbiota Signature Associated With Severity of Irritable Bowel Syndrome (2016) (PMID: 27725146 https://doi.org/10.1053/j.gastro.2016.09.049). Data are a part of a larger project where the relevance of gut microbiota for symptoms in IBS is assessed, including its interaction with other pathophysiological factors.

Data used in the article Identification of an Intestinal Microbiota Signature Associated With Severity of Irritable Bowel Syndrome, PMID: 27725146

Data från publikationen Identification of an Intestinal Microbiota Signature Associated With Severity of Irritable Bowel Syndrome (2016) (PMID: 27725146 https://doi.org/10.1053/j.gastro.2016.09.049).

Materialet är en del av ett större forskningsprojekt där betydelsen av tarmflora för symtom vid IBS (irritabel tarm) studeras, liksom dess interaktion med andra patofysiologiska variabler.

Data som använts för analys i artikeln Identification of an Intestinal Microbiota Signature AssociatedWith Severity of Irritable Bowel Syndrome, PMID: 27725146
Identification of an Intestinal Microbiota Signature Associated With Severity of Irritable Bowel Syndrome
Keywords: Irritable Bowel Syndrome; Irritabel tarmsyndrom; gut microbiota; tarmflora; HEALTH; HÄLSA; Medical and Health Sciences; Medicin och hälsovetenskap; Clinical Medicine; Klinisk medicin; Gastroenterology and Hepatology; Gastroenterologi och hepatologi; Health; Hälsa